Iodine(III)-Mediated Cyclization of Unsaturated O-Alkyl Hydroxamates: Silyl-Assisted Access to α-Vinyl and α-(2-Silylvinyl) Lactams - Wardrop, Duncan J.; Yermolina, Maria V.; Bowen, Edward G. (Synthesis, 2012)
The embodiment of lactam rings within a wealth of physiologically active natural products and pharmaceutical agents ensures that the development of synthetic methods, which facilitate the preparation of these saturated N-heterocycles, is of critical importance. Herein the development of a versatile method for the synthesis of 4 to 8-membered α-vinyl and α-(2-silylvinyl) lactams involving the iodine(III)-mediated oxidative cyclization of unsaturated O-alkyl hydroxamates, which encompass an allylsilane, is reported. Importantly, the outcome of this transformation can be effectively controlled through variation of the substitution pattern at the silicon center. While allyltrimethylsilanes undergo ring closure with desilylation to form α-vinyl lactams, the corresponding triisopropyl and triphenylsilanes cyclize without loss of the larger silyl group to form E-vinylsilanes with excellent stereoselectivity. From a mechanistic standpoint, it is proposed that this reaction proceeds via concerted alkene addition of a singlet nitrenium ion (or its equivalent) to form a bicyclic N-acyl-N-alkoxyaziridinium ion, which undergoes eliminative ring opening.
Keywords: nitrenium ion; allylsilane; hypervalent iodine; O-alkyl hydroxamate; aziridinium